EMOTIONAL STATUS AND FOOD PREFERENCE STYLE: THE RESULTS OF THE EPIDEMIOLOGICAL STUDY ESSE-RF IN SAINT-PETERSBURG, SAMARA AND ORENBURG - O. P. Rotar; Е. А. Dubinina; A. V. Orlov; R. A. Libis; E. N. Isaeva; I. R. Basyrova; D. V. Duplyakov; S. A. Gudkova; V. N. Solntsev; A. N. Alyokhin; E. I. Baranova; A. O. Konradi; et al. (Кардиоваскулярная терапия и профилактика)
Aim. To study the relation of emotional status with negative tendencies in food preference style in Russian population, including regional specifics of Saint-Petersburg, Samara and Orenburg. Material and methods. The study is the part of ESSE-RF (Epidemiology of Cardiovascular diseases in different regions of Russian Federation). Totally 1941 men and 2859 women studied at the age 25-64 y.o. — citizens of Saint-Petersburg, Samara and Orenburg. The socio- demographic data assessed, as absence/presence of cardiovascular disorders, diabetes and gastrointestinal disorders (by self-report), some parameters of the food preference style and emotional status using the Hospital Score of depression and anxiety.Results. The preference of animal fats was registered in 4,8%, daily intake of sausages in 22,4%, confectionery — in 48,4%, >6 tea spoons of sugar — in 36,5% respondents. The risk factors for pernicious habits were male gender, younger age, lower income, and tendency to spend most part of the income for food. In 51,3% of participants there were increased values on anxiety score and in 30,3% — increased depression scores. Probability of animal fats preference — odds ratio (OR)=1,89, confidence interval (CI) 95%=1,40-2,57 (p<0,001), and regular intake of sausages and meat plucks — OR=1,67, CI 95%=1,41-1,96 (p<0,01), was higher in persons with depressive states; at the same time the probability of daily intake of confectioneries and sweets was significantly lowered — OR=0,83, CI 95%=0,72-0,96 (p=0,01). Inhabitants of Orenburg and Samara had much more probably prefer sausages and animal fats comparing to Saint-Petersburg citizens, and the risk of depression was significantly variable in regions: being maximum in Orenburg — 43,9% vs 20,6% in Saint-Petersburg and 26,3% in Samara (p<0,001) without significant differences by anxiety levels. Conclusion. There is an interdependence of emotional status and food preference of a person. Emotional state, at the most related to an actualization of "pernicious" eating habits, reflects the depression. Presence of depression signs is linked with more common intake of animal fats and sausages, but less common intake of confectioneries and sweets. Interregional differences in the eating style and risks of the health disorders might probably be defined with the differences in life quality of the people.